Pembelajaran Tafsir Di Dayah Ummul Ayman Samalanga - Zainuddin Zainuddin; Zyaul Haqqi (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
Dayah Ummul Ayman is one of the largest dayah in Aceh. The teaching of tafsir in this dayah is carried out through dayah curriculum and adapted to the abilities of students. Standardization of teaching is based on the design of the subject of interpretation which is taught according to the level of learning ability of students. On the basis of this phenomenon, there are three issues discussed in this study; first, how is the pattern of learning tafsir used in Dayah Ummul Ayman; second, how is the understanding of Dayah Ummul Ayman's students in understanding of tafsir; third, what are the opportunities and challenges of the students' ability in applying learning of tafsir to Dayah Ummul Ayman. This paper shows that tafsir learning at Dayah Ummul Ayman is carried out by learning in an integrated and separate system, with learning methods such as question and answer, repetition and demonstration. The understanding of students in mastering the material of tafsir is limited to one book of tafsir, namely tafsir al-Jalalain. Santri and teachers (teungku) do not have difficulties in the learning process, but sometimes there are long discussions off-topic. Another challenge is that the students lack mastery of qawai'd tafsir because the learning only focuses on the text of the al-Jalalain commentary, whereas translation and understanding are explained by the teacher. Dayah Ummul Ayman merupakan salah satu dayah terbesar di Aceh. Pembelajaran tafsir pada dayah ini dilakukan melalui kurikulum dayah yang disesuaikan dengan kemampuan santri. Standarisasi pengajaran didasari pada rancangan mata pelajaran tafsir yang diajarkan menurut tingkat kemampuan belajar santri. Atas dasar fenomena tersebut, ada tiga persoalan yang dibahas dalam kajian ini; pertama, bagaimana pola pembelajaran tafsir yang digunakan pada Dayah Ummul Ayman; kedua, bagaimana pemahaman santri Dayah Ummul Ayman dalam memahami tafsir; ketiga, bagaimana peluang dan tantangan kemampuan santri dalam menerapkan pembelajaran tafsir pada Dayah Ummul Ayman. Tulisan ini menunjukkan bahwa pembelajaran tafsir di Dayah Ummul Ayman dilaksanakan dengan belajar secara terpadu dan terpisah, dengan metode belajar seperti tanya jawab, pengulangan dan demontrasi. Pemahaman santri dalam menguasai materi tafsir terbatas pada satu kitab tafsir saja yaitu tafsir al-Jalalain. Santri dan guru (teungku) tidak memiliki kesulitan dalam proses pembelajaran, namun terkadang ada pembahasan yang panjang di luar topik. Tantangan lainnya adalah santri kurang menguasai qawai’d tafsir karena pembelajaran hanya terfokus pada teks kitab tafsir al-Jalalain, terjemahan dan pemahaman yang dijelaskan guru.